A woman's eye : new stories by the best women crime writers - Paretsky, Sara, 1947- (Virago Press, 1992)
Crime is common ground for the twenty-one women writers in this extraordinary collection of contemporary mystery fiction.The voices here include professional crime solvers who take you from the mean streets of V.I. Warshawski's Chicago in a case of music and murder...to the California freeway where Kinsey Millhone's beloved VW skids into a shooting...to the gang-held turf of Sharon says mum's the word.And then there are mothers, grandmothers, battered wives, and social workers -- ordinary women in extraordinary situations whose voices reveal contemporary life as seen through a woman's eye.From the opening tale of a girl down-and-out in London and what she steals from a corpse...to the final story of a summer vacation in the Berkshires, complete with romance and sudden death...this unique collection brings us great mystery writing that engages both our intellects and our hearts.